DECRETO No 41.620/02, – AGREGAR – RS CARNES: UM ESTUDO DE CASO EM UMA EMPRESA DE ABATE DE BOVINOS, OVINOS E BUFALINOS - Moraes, Margareth Aparecida; Weirich, Rodrigo Herrmann; Schreiber, Dusan (Organizações Rurais & Agroindustriais, 2020)
The State of Rio Grande do Sul, through Decree No. 41.620 / 02, determined the benefit of the presumed ICMS credit based on Decree No. 37.699 / 98 of the RICMS / RS to encourage cattle, sheep and buffalo the companies that attend this branch of activity, located in this State. The objectives proposed in this research were to analyze and exemplify the importance of the company to keep pertinent information to AGREGAR-RS CARNES in accordance with the current legislation to obtain the benefit provided in Decree No. 41.620 / 02. The methodology used in this research is characterized as applied in nature, descriptive and exploratory in relation to the objectives. For the technical procedures we used bibliographical and documentary research, with non-standard interviews and case study, through a quantitative and qualitative approach. The results obtained through the analysis of data made available for the period from January 2015 to July 2016 demonstrated that there was a non-appropriation of the presumed ICMS credit due to the information not being correct in the AGREGAR-RS CARNES Program.